Immigration, regional conditions, and crime: Evidence from an allocation policy in Germany - Marc Piopiunik; Jens Ruhose (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2015)
After the collapse of the Soviet Union, more than 3 million people with German ancestors immigrated to Germany under a special law granting immediate citizenship. Exploiting the exogenous allocation of ethnic German immigrants by German authorities across regions upon arrival, we find that immigration significantly increases crime. The crime impact of immigration depends strongly on local labor market conditions, with strong impacts in regions with high unemployment. Similarly, we find substantially stronger effects in regions with high preexisting crime levels or large shares of foreigners.
urn:nbn:de:bvb:19-epub-24468-9
Keywords: F22; J15; K42; R10; 330; immigration; crime; allocation policy